Integrated industrial configurations and product-service innovation: Analysing sectoral dynamics using patent and trademark evidence - Mendonça, S.; Schmoch, U.; Neuhäusler, P. (2018 Annual Conference of EPIP, 2018)
Integrated manufacturing service systems have received attention recently. The phenomenon of services to artefacts companies, namely those specialising in intermediate goods and complex equipment, is increasingly instrumental for long run competitiveness in fast changing, high quality global markets.